Magnetic and electrical characterization of nickel-rich NiFe thin films synthesized by atomic layer deposition and subsequent thermal reduction. (25th July 2016) - Espejo, A P; Zierold, R; Gooth, J; Dendooven, J; Detavernier, C; Escrig, J; Nielsch, K
Abstract: Nickel-rich NiFe thin films (Ni92 Fe8, Ni89 Fe11 and Ni83 Fe17 ) were prepared by combining atomic layer deposition (ALD) with a subsequent thermal reduction process. In order to obtain Ni x Fe1− x O y films, one ALD supercycle was performed according to the following sequence: m NiCp2 /O3, with m  = 1, 2 or 3, followed by one FeCp2 /O3 cycle. The supercycle was repeated n times. The thermal reduction process in hydrogen atmosphere was investigated by in situ x-ray diffraction studies as a function of temperature. The metallic nickel iron alloy thin films were investigated and characterized with respect to crystallinity, morphology, resistivity, and magnetism. As proof-of-concept magnetic properties of an array of Ni83 Fe17, close to the perfect Permalloy stoichiometry, nanotubes and an isolated tube were investigated.